Travellers’ mindsets and theory of planned behaviour - Japutra, A.; Loureiro, S. M. C.; Molinillo, S.; Ekinci, Y (Tourism Management Perspectives, 2019)
Prior studies have established the importance of the theory of planned behaviour (TPB) in predicting travellers’ intentions and behaviours. However, recent research advocates that individuals’ mindsets provide an important framework for understanding their behaviour. The relationship between the two has not yet been examined. Thus, this article explores the relationship between mindsets and the theory of planned behaviour. A survey of 312 respondents was undertaken in Lisbon, Portugal. PLS-SEM was used to test the validity of the scale items and the hypotheses. The results suggest that travellers’ mindsets predict attitudes, subjective norms and perceived behavioural control.